The fish lands: German trade with Iceland, Shetland and the Faroe Islands in the late 15th and 16th century - Bart Holterman (De Gruyter Oldenbourg, 2020)
Based on newly uncovered archival sources as well as archaeological studies, this book offers the first extensive overview of the German trade with the North Atlantic in English. It challenges assumptions about the backwardness of the German North Atlantic trade, and argues that merchants did not so much rely on an old model of trading, but were adapting their trading system to the special natural and socio-economic circumstances on the islands.
Keywords: 330; Hanse; North Atlantic; Economic history